The ego in Al-Mutanabbi's poetry - Alyammahi, Shaimaa Salem (Journal of Humanities & Social Sciences, 2022)
The study focuses on the presence of the ego in Al-Mutanabbi’s poems, through the psychological, social, and psychological dimensions that this term carries, and the reasons that made this term clear and recurrent in most of Al-Mutanabbi’s poems and in the various purposes that he addressed. And through the descriptive-analytical method, it will try to explain the presence of this ego in a remarkable way that made critics and scholars flock to study his poems, the influences that affected his personality and were reflected in his poems, which became so popular that he cannot turn a blind eye to them. Clear, and explain the reasons for its presence psychologically, socially, and psychologically.
Keywords: poetry; Al-Mutanabbi’s; Ego